ANALISIS PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN - Valensia Yukke Vergiana, 08.05.51.0007; Rizal, Alimuddin (Students Journal of Economic and Management, 2012)
The purpose of this research is to investigate the effects of influence product Quality, Price Perception and service quality on satisfaction consumer. The population is the consumer who was inviting at shop and it can be transaction. After doing a literature review and hypothesis formulation, data are collected through questionnaire method of 100 respondents Dâshetwo Boutique.Which is obtained by using Accidential Sampling technique. Then, we analyze the data that is obtained by using multiple regression analysis. This analysis includes validity and reliability, multiple regression analysis, hypothesis testing by T-test and Ftest, and analysis of determination coefficien (R2) The variable of Customers Satisfaction (Y), the variable of Product Quality (X1), the variable of Price Perception (X2), the variable of Service Quality (X3), The hypothesis test usng âtâ test shows that the three independent variables analyze significantly proved to influence the dependent variable of Customersâ Satisfaction. Then through âFâ test can be known that the variable Product quality, Price Perception, and Service quality are indeed proper to test the dependent variable of Customers Satisfaction. Adjusted R figure 0,435 shows that 43,5% of Customers Satisfaction variables can be explained by the three independent variables in the regretion. While the rest 56,5% is explained by other variable beyond the model which is not analyzed in this research.Keywords : Customersâ satisfaction, Product quality, Price Perception, Service quality.